Gas-phase Fe/O and Fe/N abundances in star-forming regions: relations between nucleosynthesis, metallicity, and dust - Méndez-Delgado, José Eduardo; Kreckel, Kathryn; Esteban, C.; García-Rojas, J.; Carigi, L.; Sander, Andreas A. C.; Palla, M.; Chruślińska, M.; Looze, I. De; Relaño, M.; Giessen, S. A. van der; Reyes-Rodríguez, E.; et al. (Astronomy and astrophysics, 2024)
Context. In stars, metallicity is usually traced using Fe, while in nebulae, O serves as the preferred proxy. Both elements have different nucleosynthetic origins and are not directly comparable. Additionally, in ionized nebulae, Fe is heavily depleted onto dust grains. Aims. We investigate the distribution of Fe gas abundances in a sample of 452 star-forming nebulae with [Fe III] λ4658 detections and their relationship with O and N abundances. Additionally, we analyze the depletion of Fe onto dust grains in photoionized environments. Methods. We homogeneously determined the chemical abundances with direct determinations of electron temperature (Te), considering the effect of possible internal variations of this parameter. We adopted a sample of 300 Galactic stars to interpret the nebular findings. Results. We find a moderate linear correlation (r = −0.59) between Fe/O and O/H. In turn, we report a stronger correlation (r = −0.80) between Fe/N and N/H. We interpret the tighter correlation as evidence that Fe and N are produced on similar timescales while Fe- dust depletion scales with the Fe availability. The apparently flat distribution between Fe/N and N/H in Milky Way stars supports this interpretation. We find that when 12+log(O/H)<7.6, the nebulae seem to reach a plateau value around log(Fe/O) ≈ −1.7. If this trend were confirmed, it would be consistent with a very small amount of Fe dust in these systems, similar to what is observed in high-z galaxies discovered by the James Webb Space Telescope (JWST). We derive a relationship that allows us to approximate the fraction of Fe trapped into dust in ionized nebulae. If the O-dust scales in the same way, its possible contribution in low-metallicity nebulae would be negligible. After analyzing the Fe/O abundances in J0811+4730 and J1631+4426, we do not see evidence of the presence of very massive stars with M init > 300 M⊙ in these systems. Conclusions. The close relation observed between the N and Fe abundances has the potential to serve as a link between stellar and nebular chemical studies. This requires an expansion of the number of abundance determinations for these elements in both stars and star-forming nebulae, especially at low metallicities.
Gesehen am 11.04.2025